Historical Learning Model In Middle Vocational School - Nuraeni Marta (International Journal of Education, Information Technology, and Others, 2020)
This article is result of research on model of history teaching in SMK Ksrya Guna Manggarai, South Jakarta. The study was conductted using qualitative methods. The data of study was collected by observation, interviews and documentation. The data interviews obtained from key informants and core informants. The study produced empirical data about model of history teaching in SMK Karya Guna which includes the stages of planning, implementation and evaluation. Model of history teaching can be classifield in the conventional model of teaching whith expository strategies where instructional is centered on the teacher (teacher centeres learning). Model of history teaching in class X was all the majors almost the same pattern, using method with powerpoint media in the form of pictures. Media images used by teacher effective in helping students remember the subject matter, the learning activities more emphasis on the mastery of the content so that students can answer the exam questions in the from of memorizing facts. Thus the model of history teaching in SMK Karya Guna is focused on the transfer of knowledges has not reached the transfer of value.